Dendrolycopodium verticale comb. nov. (Lycopodiopsida: Lycopodiaceae) from China - Zhou, Xin-Mao; Zhang, Li-Bing (Phytotaxa, 2017)
A new combination in the lycophyte genus Dendrolycopodium (Lycopodiacae) from Lycopodium, D. verticale (Li Bing Zhang) Li Bing Zhang & X.M.Zhou, for a Chinese species is made.